Stress and immunity: A literature review (Research, Society and Development, 2023)
Stress significantly contributes immunosuppression, increasing infectious diseases, autoimmune manifestations and progression of neoplasms. The main cause is the increased secretion of noradrenaline and glucocorticoids in the bloodstream. With constant stress, the body begins to produce these hormones on a large scale, causing the body's own defenses to relax, which are the culprits behind the alterations in the immune system and in the cardiovascular, gastrointestinal, and metabolic systems. Stress can take different forms and contribute to symptoms of diseases, with the most common ones including headaches, insomnia, difficulty concentrating, explosive temper, upset stomach, job dissatisfaction, depression, and anxiety. This article aims to demonstrate how stress is a significant issue related to the immune system and how it directly interferes with health, leading to the onset of new pathologies or the exacerbation of existing ones. The data were obtained through a narrative literature review of articles related to the topic using the Google Scholar search engine. During the search, 58 articles were found for analysis, of which 22 were selected for the construction of the work as they met the inclusion criteria. The review showed that stress has a negative impact on the immune system, which can lead to the onset of diseases. In the face of stressful situations, the body undergoes various changes, and it is essential to understand the role of stress in the body and the concept of leading a calmer life with activities that aid in its control, reducing the risk factor.